Assessment of the application of ferrate(VI) in the treatment of agricultural irrigation water: presence of metals and Escherichia coli in fresh produce - Vargas Gutiérrez, Kryss Aracely (2023)
The aim of this study is to evaluate the effects of ferrate (VI)-based treatment on surface water collected from the Rímac River as an irrigation water treatment model for bean (Phaseolus vulgaris), lettuce (Lactuca sativa), and radish (Raphanus sativus) plant species irrigated with treated water in the experimental field. The experimental field was divided into eight 625 m2 plots (50 m × 12.5 m) with sandy loam soil (sand 51%, silt 30%, clay 19%). The treatment system operated uninterrupted for three and a half months without deterioration in production, demonstrating that it can function continuously to improve water quality even when the effects on the parameters evaluated here did not reveal significant differences, presumably due to the prevailing effect from metal concentrations already found in the soil. This study also seeks to validate the effect of treatment on the concentration of plant tissue bacteria.